Nationwide prevalence of Rickettsia felis infections in patients with febrile illness in Bangladesh. (September 2017) - Chowdhury, N.F.; Paul, S.K.; Aung, M.S.; Hossain, M.A.; Ahamed, F.; Ahmed, S.; Haque, N.; Nasreen, S.A.; Khan, S.I.; Rahman, S.M.M.; Rahman, A.S.M.M.; Ferdouse, F.; et al.
Abstract: From July 2015 to December 2016, the presence of rickettsial pathogens was investigated for 414 patients with unknown fever in eight places in all the divisions of Bangladesh. Rickettsia felis was identified in blood samples from all the regions (overall detection rate, 19.6%), suggesting nationwide prevalence of R. felis infections.